HAK IMUNITAS PELAKSANA UNDANG-UNDANG KEBIJAKAN KEUANGAN NEGARA DI MASA PANDEMI COVID-19 - Novy Listiana (Program Magister Hukum Universitas Lambung Mangkurat, 2021)
This research was conducted using a research method, the type of normative legal research, the type of norm obscurity research, the problem approach using the legal approach, conceptual approach, case approach, historical approach and a comparative approach, the nature of this research is prescriptive, the types and sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials obtained through library research. From the results of this research, it is found that first, the concept of the right to immunity that exists and is given to the implementer of the law is the concept of limited immunity rights, aka not absolute with the limitation of